2023
DOI: 10.1186/s12912-023-01470-y
|View full text |Cite
|
Sign up to set email alerts
|

Professional calling among nursing students: a latent profile analysis

Hu Jiang,
Yongxia Mei,
Xiaoxuan Wang
et al.

Abstract: Background One factor that influences nursing students' decision to pursue a nursing career is professional calling. It is important to comprehend nursing students' professional calling, which may have an impact on their career choice and career development. Objectives To investigate possible calling types and contributing variables among nursing students. Design Cross-sectional descriptive study. … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 35 publications
(35 reference statements)
0
0
0
Order By: Relevance
“…Nursing students were taught to focus on helping and caring for others. They also obtained good professional identification and professional values because of a favorable social image of nurses [ 37 ]. The recent COVID-19 pandemic has highlighted these variables [ 13 , 38 ], so it is important to understand whether they remain positively correlated post-COVID.…”
Section: Discussionmentioning
confidence: 99%
“…Nursing students were taught to focus on helping and caring for others. They also obtained good professional identification and professional values because of a favorable social image of nurses [ 37 ]. The recent COVID-19 pandemic has highlighted these variables [ 13 , 38 ], so it is important to understand whether they remain positively correlated post-COVID.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, freshmen scored significantly higher in the dimensions of experiential openness and opinion leadership than did students in other grades. Another study conducted by Jiang et al (2023), which involved 10,583 nursing students, revealed that age, gender, and place of origin were…”
Section: Current Studymentioning
confidence: 99%